2002
DOI: 10.1139/y02-062
|View full text |Cite
|
Sign up to set email alerts
|

Systemic site of action for pressor effect of angiotensin II injected into the fourth cerebral ventricle of rats?

Abstract: Angiotensin II (ANG II) causes a systemic pressor effect when injected into the cerebral ventricles. In the rat fourth ventricle, the effective doses for the ANG II pressor effect are over 100 times larger than in the systemic circulation. Considering the discrepancy of doses, the possibility that ANG II may reach the systemic circulation and promote pressor effects, following injection into the fourth ventricle, was investigated. The effects on blood pressure of different vasoactive peptides that produce pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pesquero and colleagues (54) showed that the pressor effect evoked by icv injection of ANG II results from direct stimulation of central periventricular structures and not via systemic circulation (54). Considering that ANG-(1-7) has similar chemical structure to ANG II (1 amino acid difference from the other) and in this study we used low doses compatible to other studies (32,35), we conclude that ANG-(1-7) effects obtained by central injections were restricted to the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquero and colleagues (54) showed that the pressor effect evoked by icv injection of ANG II results from direct stimulation of central periventricular structures and not via systemic circulation (54). Considering that ANG-(1-7) has similar chemical structure to ANG II (1 amino acid difference from the other) and in this study we used low doses compatible to other studies (32,35), we conclude that ANG-(1-7) effects obtained by central injections were restricted to the central nervous system.…”
Section: Discussionmentioning
confidence: 99%